Modification of Platelet Count on the Association between Homocysteine and Blood Pressure: A Moderation Analysis in Chinese Hypertensive Patients - Jianan Zhang; Jing Li; Shi Chen; Linglin Gao; Xiaoluan Yan; Mingzhi Zhang; Jia Yu; Fenchun Wang; Hao Peng (International Journal of Hypertension)
Background. Platelet consumption followed by homocysteine-induced endothelial injury suggests a crosstalk between platelet activation and homocysteine on hypertension. Platelet count has been found to modify the effect of folic acid on vascular health. However, whether platelet count could modify the contribution of homocysteine to blood pressure (BP) remains unclear. Methods. Leveraging a community-based cross-sectional survey in 30,369 Chinese hypertensive patients (mean age 62 years, 52% female), we examined the moderation of platelet count on the association between serum homocysteine and BP by constructing hierarchical multiple regression models, adjusting for conventional risk factors. If adding the interaction term of homocysteine and platelet count could explain more variance in BP and the interaction is significant, then we believe that moderation is occurring. Results. The association between serum homocysteine and diastolic BP was significantly stronger (β = 0.092 vs. 0.035, P=0.004) in participants with low platelet count (<210 × 109/L) than in those with high platelet count (≥210 × 109/L). Adding the interaction term of homocysteine and platelet count additionally explained 0.05% of the variance in diastolic BP (P=0.0001), and the interaction was significant (β = −0.021, P<0.001). Excluding participants receiving antihypertensive medications did not change our results. Conclusions. The association between homocysteine and BP was significantly stronger in participants with low vs. high platelet count and was partially moderated by platelet count. These results indicate that platelet count may be useful in the identification of individuals who are most beneficial to reducing-homocysteine treatments but this usefullness still needs further investigation.